2015
DOI: 10.1007/s12668-015-0163-z
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis, Characterization, and Antifungal Activity of the Silver Nanoparticles Against Pathogenic Candida species

Abstract: Alcoholic extract of tulsi leaves was used as a reducing and stabilizing agent for the synthesis of silver nanoparticles (AgNPs). The use of plant extract for the synthesis of nanoparticles is cost-effective, single step, and an ecofriendly process. The biosynthesized AgNPs were characterized using UV-Vis, transmission electron microscopy (TEM), X-ray diffraction (XRD), and Fourier transform infrared (FTIR) analysis. The AgNPs formed show surface plasmon resonance at 430 nm. They have a smooth surface with an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 32 publications
5
29
0
Order By: Relevance
“…These findings are in line with the results of a study by Nafisa et al which had been conducted on fungal pathogens of C. albicans, C. glabrata, and C. tropicalis. 17 Furthermore, in another study, Asghari et al investigated the antifungal effects of silver nanoparticles on Candida vulvovaginal factors in vitro. The results of this study showed that silver spherical nanoparticles with a diameter of 10 nm had antifungal activity against C. albicans to some degree.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are in line with the results of a study by Nafisa et al which had been conducted on fungal pathogens of C. albicans, C. glabrata, and C. tropicalis. 17 Furthermore, in another study, Asghari et al investigated the antifungal effects of silver nanoparticles on Candida vulvovaginal factors in vitro. The results of this study showed that silver spherical nanoparticles with a diameter of 10 nm had antifungal activity against C. albicans to some degree.…”
Section: Discussionmentioning
confidence: 99%
“…Candida spp. have also developed a battery of putative virulence factors which include adherence to host tissues, yeast hyphal transitions, and secretion of hydrolytic enzymes especially secretion of proteinases and phospholipases known to be frequently associated with pathogenicity [2]. Secreted aspartyl proteinases (S aspartyl proteinases) by Candida spp.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we present the synthesis and characterization of Fe 3 O 4 /Ag nanoparticles obtained by two-step laser ablation of iron and silver targets in pure water, in order to obtain colloidal suspensions with magnetic properties, along with spectral tests demonstrating their SERS activity. Silver is by far the most suitable metal to provide SERS intensification, apart from marked anti-bacterial, antifungal and anti-inflammatory activities [12][13][14][15], as previously said. Fe 3 O 4 magnetic nanoparticles present good biocompatibility and low toxicity [16][17][18] and are therefore widely used in biomedical applications.…”
mentioning
confidence: 86%